Pronunciation Indonesian Sounds By Speakers Foreign : A Phonological Study (PT. LARPA JAYA PUBLISHER, 2023)
Background back : Important Indonesian no only hold role important in scale national , but also play a role in global scale as Language foreign . this become basis and motivation they For Can Indonesian . So from that , a lot speaker who started interested For Study Indonesian and fluent in its use . Learning Indonesian for speaker foreign neither is this only done in Indonesia, will but Already Lots seller Indonesian for speaker foreign exchange (BIPA) . teaching abroad , here prove that tall enthusiasts speaker foreign For learn and master Indonesian . The variety activity it requires they For communicate One each other, fine That with colleague business nor other communities in Indonesia. Goals : goals study This is For know sounds what is difficult in Indonesian pronounced with right by the speaker foreign and the position where the sounds That difficult pronounced. Method : Method research This is method descriptive so that the data in the form of a consonant word obtained from results interaction with speaker Foreigners who are at the UMSU BIPA Institute . Result : For get inside data study this , researcher can obtain text reading recording the sound produced by the respondent . researcher find 30 pronounced consonant vocabulary speaker foreign to in Language Indonesia. Conclusion : difficulty pronunciation experienced by the speaker foreign origin Cambodia caused how strong influence Language mother ( language kmher ) so often No realize appropriate pronunciation Language indonesia. difficulty pronunciation consonant Indonesian often Experienced by speakers foreign Cambodia in a manner general despicable be , consonant / b/ /d/ /p/ , /m/ /t/ /s/ , and /k/ / i / /l/.